The aggregation of heterogeneous metadata in web-based cultural heritage collections: a case study. (1st January 2013) - Peroni, Silvio; Tomasi, Francesca; Vitali, Fabio
In this paper, we discuss some issues related to digital libraries that are born as aggregators of cultural heritage resources harvested from different distributed digital repositories. Whenever such aggregations fall short of providing a real service to users, most of the time this is due to the inadequacy of the data (or conceptual) model proposed for the mapping and exposed to the final user. Our aim is to enhance the formal representation of cultural heritage materials, reasoning about some key concepts to improve the quality of the description of digital resources by refining the conceptual model. In order to discuss about these issues, we focus particularly on Europeana, the principal European Digital Library, as the foremost and most paradigmatic example of aggregators, and on the Europeana Data Model (EDM) as the conceptual model on which metadata from different repositories are mapped in Europeana.